ANALISIS PROSES PEMBELAJARAN LITERASI DAN NUMERASI DASAR INKLUSIF SELAMA PANDEMI COVID-19 - Widodo, Arif; Haryati, Linda feni; Syazali, Muhammad; Indraswati, Dyah; Anar, Ashar Pajarungi (PGSD UNIKA SANTU PAULUS RUTENG, 2022)
Inclusive learning is one solution amid the diverse abilities of students in schools, especially in the areas of literacy and numeracy. This study aims to analyze the implementation of inclusive literacy and numeracy learning in elementary schools. The focus of the study in this research is whether the school has implemented inclusive learning well? how is inclusive learning done? what are the obstacles faced by teachers in implementing inclusive learning? This research uses a descriptive qualitative approach. The use of this approach is based on a description of the teacher's behavior, perceptions, motivations, and actions during the implementation of inclusive literacy and numeracy-based learning. Data collection methods in this study include interviews, observation, and documentation. The instruments in this study include observation sheets for data collection in the field, interview guidelines conducted to confirm the learning activities carried out, and documents found in the field. The data analysis process includes the stages of data reduction, data presentation, and concluding. The results of the study found that schools had implemented inclusive literacy and numeracy learning well. The learning stages include building student readiness, reading stories/substations, and learning according to level. The biggest obstacles faced by teachers in inclusive literacy and numeracy learning are that some students refuse to be grouped based on level, the number of students who experience hyperactivity disorders, and protests from parents when students are grouped to a lower level.